Does Moving Average Technical Trading Rule Provide Value for Intraday Stock Trading?: Evidence from the Indonesia Stock Exchange - Harsanto, Ario; Ekaputra, Irwan Adi (UI Scholars Hub, 2012)
This paper analyzes the value of employing simple moving average (SMA) and moving average (MA) technical trading rules for intraday stock trading in the Indonesia Stock Exchange. We test independently SMA[5], SMA[10], SMA[15], MA[5,50], MA[5,150], and MA[5,200] trading rules. We ﬁnd all three SMAs and MA[5,200] tend to deliver returns greater than the unconditional basic return (UBR), while MA[5,50] and MA[5,150] generate returns less than UBR. We conclude that SMAs are more valuable than MAs as intraday technical trading rules.